A New Way Forward: How Brain SPECT Imaging Can Improve Outcomes and Transform Mental Health Care Into Brain Health Care - Amen, Daniel G.; Easton, Michael (Frontiers in Psychiatry, 2021)
Abstract Over the past 30 years, brain single photon emission computed tomography (SPECT) imaging has developed a substantial, evidence-based foundation for numerous indications relevant to psychiatric practice, including dementia, brain trauma, cerebrovascular disease, seizures, and complex or treatment resistant neuropsychiatric presentations. Unfortunately, SPECT in clinical practice is utilized by only a very small fraction of psychiatric clinicians. This article presents a rationale for shifting the paradigm to one that includes a more widespread use of SPECT in clinical practice, especially for complex cases, including seven clinical applications. Adding neuroimaging tools like SPECT to day-to-day clinical practice can help move psychiatry forward by transforming mental health care, which is stigmatizing and often shunned by the general public, to brain health care, which the authors argue will be more likely to be embraced by a larger group of people in need.